Cardiovascular Risks of Methylphenidate in Children with ADHD - Czachor, Adrianna; Servaas, Elwira; Kotula, Alicja; Haber, Mateusz; Grelewicz, Olga; Kucy, Natalia; Juśkiewicz, Adam; Kula, Paula (Journal of Education, Health and Sport, 2024)
Introduction: Attention Deficit Hyperactivity Disorder (ADHD) is a prevalent neurodevelopmental disorder affecting millions of children worldwide. Methylphenidate is one of the most prescribed medications for managing ADHD symptoms due to its proven efficacy. However, despite its widespread use and effectiveness, there are ongoing concerns about the cardiovascular safety of methylphenidate, particularly in pediatric populations. These concerns stem from reports of increased heart rate, elevated blood pressure, and, in rare cases, more severe cardiovascular events. Aim of the Study: To review recent studies on the cardiovascular safety of methylphenidate in children with ADHD, synthesizing findings to inform clinical practice. Materials and Methods: A comprehensive literature review was conducted, focusing on studies published in the last decade that investigated the cardiovascular effects of methylphenidate in children with ADHD. Conclusion: The review highlights that while methylphenidate is generally well-tolerated, there are notable cardiovascular risks, particularly in susceptible children. These risks underscore the importance of thorough cardiovascular assessment and monitoring in children undergoing treatment with methylphenidate. The findings advocate for a balanced approach where the benefits of symptom management are weighed against potential cardiovascular risks. Clinicians are advised to adopt comprehensive monitoring strategies and consider individual risk factors when prescribing methylphenidate to children with ADHD.